2019
DOI: 10.21873/anticanres.13863
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure–Cytotoxicity Relationship of 2-Styrylchromones

Abstract: Background/Aim: Studies of biological activity of 2styrylchromone derivatives focusing on antioxidant, antiinflammatory, antiviral and antitumor activity are limited. In this study, eighteen synthetic 2-styrylchromone derivatives were investigated for their cytotoxicity against human malignant and non-malignant cells, and then subjected to quantitative structure-activity relationship (QSAR) analysis. Materials and Methods: Tumor-specificity was calculated by the ratio of mean 50% cytotoxic concentration (CC 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…We found that TS value (D/B in Table I) of two 3styrylchromones [7,14] (TS=301.1, 182.0) is much higher than the maximum TS values of 3-(N-cyclicamino)chromones (TS=12.3) (17), pyrano [4,3-b]chromones (TS=47.8) (18), 2arylazolylchromones and 2-triazolylchromones (TS=21.2) (19) and 2-styrylchromones (TS=89.1) (20). This suggests that [7,14] can be lead compounds for designing new types of anticancer drugs.…”
Section: Against Four Human Oscc Cell Lines Ca9-22 (•) Hsc-2 (■) Hmentioning
confidence: 98%
“…We found that TS value (D/B in Table I) of two 3styrylchromones [7,14] (TS=301.1, 182.0) is much higher than the maximum TS values of 3-(N-cyclicamino)chromones (TS=12.3) (17), pyrano [4,3-b]chromones (TS=47.8) (18), 2arylazolylchromones and 2-triazolylchromones (TS=21.2) (19) and 2-styrylchromones (TS=89.1) (20). This suggests that [7,14] can be lead compounds for designing new types of anticancer drugs.…”
Section: Against Four Human Oscc Cell Lines Ca9-22 (•) Hsc-2 (■) Hmentioning
confidence: 98%
“…Uesawa and co-workers [ 66 ] investigated the cytotoxic activity of 2-SC 1 , 30 , 56 , 58 , 88 , 92 , and 104 – 115 ( Figure 39 ) against four human oral squamous cell carcinoma (Ca9-22, derived from gingival tissue; HSC-2, HSC-3, and HSC-4, derived from tongue) and three human oral mesenchymal cells (HGF, HPLF, and HPC). Cytotoxic activity was assessed by the MTT assay, and the results were presented as CC 50 , for each cell line (without the associated error) and the mean values of the four tumor cell lines and the three normal cells (with the associated error), SI, and potency-selectivity expression (PSE).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The subG 1 population is a marker of apoptosis. Thus, these two 2-SC induced apoptosis of HSC-2 cell more potently than the positive control, actinomycin D (1 μ M) [ 66 ]. The results obtained for 2-SC 58 were in line with those obtained in the previous study [ 65 ], where this 2-SC demonstrated an antiproliferative and microtubule-stabilizing effect [ 65 ].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…We investigated a total 291 compounds from 17 different groups ( A~Q ) of their cytotoxicity (assessed by CC 50 ) against four human OSCC (Ca9-22, HSC-2, HSC-3, and HSC-4) and three human normal mesenchymal cells (HGF, HPLF, and HPC), and then their tumor specificity (assessed by TS M , calculated as describe in Figure 2 , and potency-selectivity expression (PSE)) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. PSE, that reflects both tumor specificity and cytotoxicity against tumor cells, was calculated by dividing the TS M by CC 50 for tumor cells, and then multiplying by 100.…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%
“…This demonstrated that only limited numbers of compounds show higher tumor specificity, although their structures are very similar with each other. It is possible that such highly tumor-specific compounds show the optimal 3D structure, since the tumor specificity of chromone compounds shows the tight correlation with chemical descriptors that reflect the 3-D structure ( Table 4 ) [ 33 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Development Of Newly Synthesized Chromone Derivatives Witmentioning
confidence: 99%